Clinical Interpretations of Patient Experience in a Trial of Psilocybin-Assisted Psychotherapy for Alcohol Use Disorder - Bogenschutz, Michael P.; Podrebarac, Samantha K.; Duane, Jessie H.; Amegadzie, Sean S.; Malone, Tara C.; Owens, Lindsey T.; Ross, Stephen; Mennenga, Sarah E. (Frontiers in Pharmacology, 2018)
After a hiatus of some 40 years, clinical research has resumed on the use of classic hallucinogens to treat addiction. Following completion of a small open-label feasibility study, we are currently conducting a double-blind placebo-controlled clinical trial of psilocybin-assisted treatment of alcohol use disorder. Although treatment effects cannot be analyzed until the study is complete, descriptive case studies provide a useful window into the therapeutic process of psychedelic-assisted treatment of addiction. Here we describe treatment trajectories of three participants in the ongoing trial to illustrate the range of experiences and persisting effects of psilocybin treatment. Although it is difficult to generalize from a few cases, several qualitative conclusions can be drawn from the data presented here. Although participants often find it difficult to describe much of their psilocybin experience, pivotal moments tend to be individualized, extremely vivid, and memorable. Often, the qualitative content extends beyond the clinical problem that is being addressed. The participants discussed in this paper experienced acute and lasting alterations in their perceptions of self, in the quality of their baseline consciousness, and in their relationship to alcohol and drinking. In these cases, experiences of catharsis, forgiveness, self-compassion, and love were at least as salient as classic mystical content. Finally, feelings of increased "spaciousness" or mindfulness, and increased control over choices and behavior were reported following the drug administration sessions. Ultimately, psilocybin-assisted treatment appears to elicit experiences that are extremely variable, yet seem to meet the particular needs of the individual.